2013
DOI: 10.4049/jimmunol.1201854
|View full text |Cite
|
Sign up to set email alerts
|

GITR-Dependent Regulation of 4-1BB Expression: Implications for T Cell Memory and Anti–4-1BB–Induced Pathology

Abstract: The TNFR family member 4-1BB plays a key role in the survival of activated and memory CD8 T cells. However, the mechanisms that regulate 4-1BB re-expression on memory CD8 T cells after Ag clearance are unknown. In unimmunized mice, ∼10% of CD8 CD44hi memory T cells in the bone marrow (BM) and liver express 4-1BB, with minimal 4-1BB expression in spleen and lymph node. IL-2, IL-15, and IL-7 are collectively dispensable for 4-1BB expression on the memory CD8 T cells. Rather, T cell–intrinsic glucocorticoid-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 53 publications
1
30
2
Order By: Relevance
“…IL-15 can up-regulate the expression of GITR in memory CD8 T cells [27] and the presence of GITR on memory CD8 T cells is required for their persistence in vivo [28]. Confirming previous results, we found that IL-15 increased GITR expression in a dose-dependent fashion in our model ( Figure 6).…”
Section: Role Of Gitr In Il-15 Protective Effectsupporting
confidence: 81%
See 2 more Smart Citations
“…IL-15 can up-regulate the expression of GITR in memory CD8 T cells [27] and the presence of GITR on memory CD8 T cells is required for their persistence in vivo [28]. Confirming previous results, we found that IL-15 increased GITR expression in a dose-dependent fashion in our model ( Figure 6).…”
Section: Role Of Gitr In Il-15 Protective Effectsupporting
confidence: 81%
“…However, significantly higher level of GITR in the presence of increasing doses of IL-15 shows that GITR could be involved in the antiapoptotic effect of IL-15. This TNFR family member is essential for the 4-1BB receptor expression on memory CD8 T cells as well as their survival in vivo [28]. GITR is also known to interact with the TNF associated factor (TRAF1, TRAF2 and TRAF3), which downstream signaling leads to enhanced survival of the CD8 memory T cells [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agonist anti-OX40 has no effect on viral load in LCMV cl 13 infection (11), and agonist anti-4-1BB had minimal therapeutic effect when administered during the chronic stage of LCMV cl 13 infection due to the loss of a key signaling adaptor, TNFR-associated factor (TRAF)1, downstream of 4-1BB, with similar findings in T cells from chronically HIV-infected donors (12). Although anti-4-1BB demonstrated efficacy when combined with IL-7, which restores TRAF1 levels (12), there is growing concern that agonist therapies targeting T cell cosignaling molecules such as 4-1BB and CD28 or soluble factors such as IL-21 may induce indiscriminate or overzealous expansion of CD8 T cells and result in immune pathology (13)(14)(15)(16)(17)(18). Therefore, it remains a significant challenge to identify a T cell costimulatory molecule that is both safe and effective in improving immune function and control of viral infections.…”
mentioning
confidence: 79%
“…For example, in a 3 day-bromodeoxyuridine (BrdU)-labelling analysis, the average frequency of dividing antigen-specific memory CD8 + T cells was 4% in the bone marrow and 2% in the spleen 4 . Moreover, when carboxyfluorescein succinimidyl ester (CFSE)-labelled antigen-specific memory CD8 + T cells were transferred into non-immunized animals, they showed higher rates of proliferation in the bone marrow than in the spleen and lymph nodes 3,10 . In general, the data concerning memory CD8 + T cell cycling in the bone marrow are all in agreement.…”
Section: Francesca DI Rosamentioning
confidence: 99%